Pengaruh Work Family Conflict Dan Family Work Conflict Terhadap Stres Kerja Dosen Perempuan Unisma (Universitas Islam Malang) - Aris Setyawan; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis research was conducted with the aim of analyzing the effect of Work Family Conflict and Family Work Conflict on the Job Stress of Female Lecturers at Islamic University of Malang. The population in this study were 152 female lecturers at the university. The sampling technique used is proportional stratified random sampling wherein this technique is for selecting samples based on class. The analytical method used in this study is multiple linear regression analysis with hypothesis testing using the t test and f test. From this study produced answers that have been previously processed that Work Family Conflict and Family Work Conflict simultaneously affect Work Stress, Work Family Conflict affects Work Stress and Family Work Conflict Against Work Stress.Keywords: Work Family Conflict, Family Work Conflict and Work Stress